Joyful encounters in performance art - Sousa, Heloísa Helena Pacheco de (Farol, 2022)
Considering the suggestion of a relational aesthetic to think about pieces created after the avant-gardes, we are faced with interactive propositions that present the relationship as the founding experience. This analysis is confronted with some criticism that problematize the democratic quality assumed in the interactions, when they disconsider the dissent between the people involved. Understanding the relational field as derived from encounters, I suggest to consider the joinful affections on these interactions, their ethical dimensions and political urges.